1998
DOI: 10.1093/019829414x.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Ideologies and Political Theory

Abstract: Provides a novel approach to the analysis of ideologies, through examining their internal conceptual morphology. The result is to interpret ideologies as particular combinations of meaning from an indeterminate range of meanings at the disposal of a society—a process identified as the decontestation of the essentially contestable. This accounts for ideological flexibility and for the overlap, continuous transformation, and regrouping of ideological families. Ideological cores are refined by the adjacent and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
147
0
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(162 citation statements)
references
References 63 publications
0
147
0
15
Order By: Relevance
“…Ideologies, like liberalism and conservatism, crashed and bounced off each other, morphing and redefining themselves over the field of political activity for the purpose of binding people to a particular course of action. 94 This morphological, technique shared elements of its wider approach with the Cambridge school of political thought which, in the 1970s and 80s, had involved a similar analytic of ideology as the study de-contested meaning through which historical societies constituted their political culture. alter-ideology of global significance, the antagonist to their earlier notion of globalism.…”
Section: B Ideational and Functionalist Ideologymentioning
confidence: 99%
“…Ideologies, like liberalism and conservatism, crashed and bounced off each other, morphing and redefining themselves over the field of political activity for the purpose of binding people to a particular course of action. 94 This morphological, technique shared elements of its wider approach with the Cambridge school of political thought which, in the 1970s and 80s, had involved a similar analytic of ideology as the study de-contested meaning through which historical societies constituted their political culture. alter-ideology of global significance, the antagonist to their earlier notion of globalism.…”
Section: B Ideational and Functionalist Ideologymentioning
confidence: 99%
“…Michael Freeden (1996) suggested that there are some ideologies which can be combined with other main ideologies. Populism, as the literature shows, is one example of those (Albertazzi and McDonnell, 2008;Jagers and Walgrave, 2007;Lucardie and Voerman, 2012;Mudde, 2004;Stanley, 2008;Taggart, 2000).…”
Section: Right-wing Populism: What Do We Mean?mentioning
confidence: 99%
“…S jedne strane, populizam uvijek ima središnju jezgru koja obuhvaća pozitivno referiranje na narod i antielitizam, ali, s druge strane, dodatni ideološki elementi, ako ih neki populizam iskazuje, mogu biti različiti i stoga ne mogu predstavljati definicijska obilježja. Pokušavajući prihvatiti ovo razlikovanje populizma i "pravih" političkih ideologija, dio istraži-vača (primjerice, Stanley, 2008) smatra kako se na populizam može primijeniti koncept "slabe" (thin) ideologije, što ga je razvio Michael Freeden (1996Freeden ( , 2003. Prema Freedenu (2003, str.…”
Section: šTo Je Populizam?unclassified